A Conserved Potential Development Framework Applies to Shoots of Legume Species with Contrasting Morphogenetic Strategies - Faverjon, Lucas; Escobar-Gutiérrez, Abraham J.; Litrico, Isabelle; Louarn, Gaëtan (Frontiers in Plant Science, 2017)
A great variety of legume species are used for forage production and grown in multi-species grasslands. Despite their close phylogenetic relationship, they display a broad range of morphologies that markedly affect their competitive abilities and persistence in mixtures. Little is yet known about the component traits that control the deployment of plant architecture in most of these species. During the present study, we compared the patterns of shoot organogenesis and shoot organ growth in contrasting forage species belonging to the four morphogenetic groups previously identified in herbaceous legumes (i.e., stolon-formers, rhizome-formers, crown-formers tolerant to defoliation and crown-formers intolerant to defoliation). To achieve this, three greenhouse experiments were carried out using plant species from each group (namely alfalfa, birdsfoot trefoil, sainfoin, kura clover, red clover, and white clover) which were grown at low density under non-limiting water and soil nutrient availability. The potential morphogenesis of shoots characterized under these conditions showed that all the species shared a number of common morphogenetic features. All complied with a generalized classification of shoot axes into three types (main axis, primary and secondary axes). A common quantitative framework for vegetative growth and development involved: (i) the regular development of all shoot axes in thermal time and a deterministic branching pattern in the absence of stress; (ii) a temporal coordination of organ growth at the phytomer level that was highly conserved irrespective of phytomer position, and (iii) an identical allometry determining the surface area of all the leaves. The species differed in their architecture as a consequence of the values taken by component traits of morphogenesis. Assessing the relationships between the traits studied showed that these species were distinct from each other along two main PCA axes which explained 68% of total variance: the first axis captured a trade-off between maximum leaf size and the ability to produce numerous phytomers, while the second distinguished morphogenetic strategies reliant on either petiole or internode expansion to achieve space colonization. The consequences of this quantitative framework are discussed, along with its possible applications regarding plant phenotyping and modeling.